Impact of regular relaxation training on the cardiac autonomic nervous system of hospital cleaners and bank employees. - Toivanen, H; Lansimies, E; Jokela, V; Hanninen, O (Scandinavian Journal of Work, Environment & Health, 1993)
The work-related strain of 50 female hospital cleaners and 48 female bank employees was recorded during a period of rationalization in the workplace, and the effect of daily relaxation to help the workers cope was tested. The subjects were arranged into age-matched pairs and randomly allocated into intervention and reference groups. The intervention period lasted six months. The relaxation method was brief and easily introduced as an alternative break in the workplace. Each training session lasted 15 min. A microcomputer-based system was used to record heart rate variability in response to quiet breathing, the Valsalva maneuver, deep breathing, and active orthostatic tests. Cardiac reflexes indicated that occupational strain (especially of a mental nature) caused the functioning of the autonomic nervous system to deteriorate. Regular deep relaxation normalized the function and improved the ability to cope.